Development of mechanism for entertainment device - Maria Katalina Bonilla-Ramírez; Karol Geraldinne Torres-Pachón; Stefany Puentes-Cantor; Karen Juliette Forero-Rubio; Yolanda Torres-Pérez; Edwin Yesid Gómez-Pachón (Visión Electrónica, 2019)
The objective of this project is based on the design and manufacture of a mechanism for a didactic product, awakening the interest of those who have affinity to horses and their skills. It is intended for people between 20 and 50 years old.